Analysis Impact of Coronavirus in the Kingdom of Saudi Arabia by Using the Artificial Neural Network - Tasneem Kamal Aldeen Muhamed; Mona Yahya Salim Alfefi; Nahla Morad (Eximia, 2022)
We suggested an artificial neural network (ANN) in a medical model for covid-19 patients in this study, and we interfaced their medical data Symptoms that accompany the disease before and after the medical examination. The findings of the questionnaire were displayed. Using a specific neural network for analysis It’s possible that the results will be extremely precise. The results revealed that applying style (ANN) to estimation yielded high-precision results. The symptoms of the new sickness were also investigated.